A Comparative Analysis of First-Difference GMM and System GMM Approaches on Economic Growth - Hendayanti, Ni Putu Nanik; Nurhidayati, Maulida; Soraya, Siti; Sufahani, Suliadi Firdaus; Ismoen, Muhaimin (Universitas Muhammadiyah Mataram, 2025)
One of the critical causes of Indonesia's economic growth is the presence of the Covid-19 Pandemic which has resulted in a decline in public consumption and investment interest at the household level in each region. One of the areas with a decrease in the number of affected tourist visits is Bali Province. This is because Bali is an icon of Indonesia and is the best tourist destination. The purpose of this study is to obtain the most suitable model to model economic growth with the FD-GMM and Sys-GMM approach meeting the criteria of validity, consistency, and unbiased. This type of research is quantitative research with data sourced from the central statistical agency of Bali Province. The method used in this study is to compare the First-Difference Generalized Method of Moment (FD-GMM) and System Generalized Method of Moment (Sys-GMM) on economic growth data in Bali Province. The result of this study is the estimation of model parameters with the approach FD- GMM meets valid, consistent, and unbiased criteria. In contrast, the estimation of model parameters with the Sys-GMM meets validity and consistency criteria. However, the unbiased criteria are not met because the resulting model has a biased coefficient. The best model used to model Bali's economic growth data is the FD-GMM model. The above results imply that the existence of the population categorized as poor and the existence of the workforce are still a special concern. So, the suggestion in this study is that it is necessary to conduct a policy analysis from the Bali Provincial Government in dealing with poverty rates. Furthermore, employment management in Bali will be reorganized to be more directed and measurable in increasing the economic growth of Bali Province.